Fungal infection among patients with chronic rhinosinusitis who underwent endoscopic sinus surgery - Gautham Varun, Krishna Mohan; Kanitha, M. Senthil; Rejitha, I. M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Chronic rhinosinusitis (CRS) involves persistent inflammation of the nasal passages and sinuses, often attributed to Aspergillus species as a primary etiological agent. Effective treatment involves complete eradication of fungal pathogens and restoration of sinus function, commonly achieved through functional endoscopic sinus surgery (FESS). This study aimed to evaluate the clinical and radiological features, assess the prevalence and identify the mycological profile of fungal rhinosinusitis. Methods: This study was a prospective observational analysis involving a cohort of 50 patients treated at the Tirunelveli Medical College between June 2017 and July 2017. Nasal sinus tissues and secretions were collected for mycological and bacteriological analysis. Samples were processed on the same day, with fungal elements identified via KOH mount and cultured on Sabouraud dextrose agar. Bacterial cultures were grown on MacConkey agar and species identification was performed using biochemical tests. Results: Fungal culture results showed that 72% of the patients had a negative culture, while 28% had a positive culture. Among the 50 patients, 36 did not have diabetes or hypertension. All sinuses were involved in 40 patients and 24 had nasal polyps, with bilateral polyps being the most common. The most frequently isolated fungal species was Aspergillus. KOH positivity was strongly correlated with culture positivity, with 9 out of 10 KOH-positive patients also being culture-positive, while KOH negativity was associated with culture negativity in 35 out of 36 patients. Conclusions: CRS significantly affects quality of life, with fungal infections being a notable cause, especially in patients with unilateral sinus involvement. Effective treatment requires endoscopic sinus surgery, followed by antifungal therapy.